Krupei N. V. Portrait description in translation (based on T. Shevchenko’s story “The artist” and its English translations by A. Bilenko, John Weir and P. Selver) - Krupei N. V. (Philological Treatises, 2020)
The article focuses on the analysis of reproduction of the portrait description in translation. In the research the general characteristics of T. Shevchenko‟s story “The Artist” is provided, the notion of portrait description is introduced as well as the stylistic and linguistic peculiarities of the story from the perspective of translation studies are under analysis. The article consideres the ways of verbalization of the Artist‟s portrait in the English translation of the story done by A. Bilenko, John Weir and P. Selver.